Teaching of the American Independence in Colombia and Spain textbooks 2009-2011 - Soto Arango, Diana Elvira; Bernal Villate, Sandra Liliana; Pacheco Vargas, William; Espinosa, Yules Alejandro; Paternina Soto, Liliana; Perelló, Beatriz (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper presents the findings of the investigation "Teaching of the American Independence in Colombia and Spain. 2009-2011", which analyzed how the issue of the American Independence from the school and the classroom (along with the contents, messages, iconography of texts, guides, and teaching and learning processes) originated some social imaginaries in students of basic primary education (4 and 5), who assimilate them towards a new identity in the imaginary of the nation in the Cundi-Boyacense region of Colombia and in 2 ESO and 4 High School of the Province of Andalusia, Spain. It recognizes the history of education within the local socio- educational context where teaching and learning processes are delimited in public and private educational institutions that carry contents, messages, social imaginaries and iconography on the subject of the American Independence. It presents a reflection on problems related to the production of ideologies, imaginaries and mentalities. That is, problems belonging to the field of social representations. It was used the compared methodology approaching the social mapping, from the spatial imagination. It was concluded that the socio-cultural contexts of the institution and the country lead to different insights and imaginaries on the subject of the American independence in the teaching and learning processes of Colombia and Spain.